Health-aware fault-tolerant receding horizon control of wind turbines. (February 2020) - Jain, Tushar; Yamé, Joseph
Abstract: Actuator faults in wind turbines (WT) significantly increase the structural loads exhibited by torsional vibration and tower fore-aft bending, thereby, drastically hampering the turbine health in terms of the reduction in its lifetime. This paper presents a health-aware fault-tolerant control (HAFTC) scheme for WT such that the turbine health, i.e., power maximization and fatigue reduction, can be achieved even under the event of bias faults in converter actuator. The proposed HAFTC system is built upon two interconnected modules: fault diagnosis and controller reconfiguration. The latter module is developed using a receding horizon control technique where the underlying optimization problem is not convex. The originality of the proposed scheme lies in the transformation of the initial non-convex optimization problem into a convex problem. The former module extracts the complete information of the fault, which is constructed using an unknown-input-observer based residual filter and a specific fault-estimation filter. A 2 M W WT system is used to demonstrate the effectiveness of the HAFTC scheme. Highlights: Operation and maintenance costs of wind turbines (WT) are impacted by fatigue loads. Pitch and converter actuator faults increase significantly these fatigue loads. A Health-aware fault-tolerant control scheme for wind turbines is proposed. A realizable Receding horizon control reconfiguration technique for WT is developed. A specific fault estimation filter is proposed to estimate convertor faults.